Efficacy of Mifepristone/Misoprostol Combination for Medical Abortion Determined by Detection of Retained Products in a Community Hospital in Taipei, Taiwan - Szu-Yuan Chou; Tsung-Ming Chang; Pui-Ki Chow; Chih-Fen Wu; So-Jung Liang; Chun-Sen Hsu (Taiwanese Journal of Obstetrics & Gynecology, 2004)
Objective: The oral mifepristone/misoprostol combination (MMC) is safe for medical abortion in early pregnancy. The rate of complete abortion in MMC-treated pregnancies at a community hospital in Taipei, Taiwan, was determined by ultrasonography and histopathology. Materials and Methods: A total of 149 women who asked for legal termination of pregnancy before 49 days since the last menstruation were given 600 mg of oral mifepristone followed by 600 μg misoprostol 48 hours later. After 14 days, all women who had vaginal spotting or bleeding and in whom transvaginal ultrasonography demonstrated an endometrial thickness of more than 10 mm underwent vacuum aspiration or therapeutic dilatation and curettage (D&C). Specimens were identified by histopathology. Results: A total of 108 women had complete abortions without the need for surgical intervention. Of 41 women who underwent vacuum aspiration or therapeutic D&C, histopathology showed that nine had decidual tissue, 29 had gestational tissue, and three had ongoing pregnancies. Conclusion: In this study, the complete abortion rate was 78.5% after oral MMC.